2021
DOI: 10.1111/cuag.12269
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Persistence and Potentials on the Edge of Northern Ontario

Abstract: Drawing on farmers' lived experiences, I explore factors that shape agricultural persistence in the Parry Sound District, Ontario, Canada. Local farming is embedded in broader contexts and is place-based and specific. Agricultural persistence and resilience are shaped in part through individual factors, such as flexibility in response to change, the valuing of local agricultural heritage, and the determination to farm. However, attention to specific agricultural needs is critically necessary to help ensure agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…For agriculturalists whose farms have been passed down from generation to the next, the loss of a farm is the loss of a familial legacy. Farming professions are tied to a rural identity and a way of life (see also Finnis, 2021). Returning to Ted Brown's quote from the start of this article, “Without water, it's all over.” The inability to irrigate crops is a future scenario almost too bleak to consider—a paralyzing future scenario.…”
Section: Resultsmentioning
confidence: 99%
“…For agriculturalists whose farms have been passed down from generation to the next, the loss of a farm is the loss of a familial legacy. Farming professions are tied to a rural identity and a way of life (see also Finnis, 2021). Returning to Ted Brown's quote from the start of this article, “Without water, it's all over.” The inability to irrigate crops is a future scenario almost too bleak to consider—a paralyzing future scenario.…”
Section: Resultsmentioning
confidence: 99%
“…The materials used in the series of ceremonies are natural and easily recyclable, so the burial of buffalo heads also decomposes in to the soil without problems. Agricultural products and animals dissolved in the soil are easily degraded (Finnis, 2021).…”
Section: Unan-unanmentioning
confidence: 99%
“…This research has shown us that the success of such programs depends on: (a) the involvement of Elders, who provide youth with the traditional knowledge needed to access the spirituality of the natural world; (b) the inclusion of opportunities for youth to engage in outdoor activities, which allow them to learn and rehearse Native skills; and (c) the involvement of Indigenous youth in planning and executing the activities, which allows them to "be the change" that they want to see in the world around them. Prompt is from Finnis (2021), an open-access article. Some agricultural shifts have been more abrupt, leaving farmers with no real ability to respond in any way other than crisis management.…”
Section: This Includes [Insert]mentioning
confidence: 99%